The importance of physical activity and fitness programs in older people: a Systemic review - Marina Vukotic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2018)
Several studies have dealt with costing diff erent factors of physical fi tness, and to investigate diff erences in physical fi tness indicators depending on the size of the body mass index. Therefore, the purpose of this study is to research which would summarize potential factors of physical fi tness in one place and their diff erences in fi tness indicators depending on the size of the body mass index. The Google Scholar scientifi c database was used in this research, while all available materials were included in the analysis conducted by september 15, 2018. The fi eld of search of the listed electronic database of original scientifi c papers referred to the application of various fi tness programs in older people. The following keywords were used in the search for the listed database: "physical activity", "fi tness", "older people" and "body mass index". Based on body mass index, respondents are in relation to sex, divided into groups: persons with normal body weight and persons with increased body weight. On the other hand, a signifi cant diff erence was found in the indicators of functional fi tness, depending on the body weight in favor of persons with normal body weight on subunits of women and men of older age.